Economic dimensions of Covid-19 in Indonesia : responding to the crisis - Lewis, Blane D.; Witoelar, Firman (Singapore : ISEAS-Yusof Ishak Institute, 2021)
Beginning in December 2019, the coronavirus swept quickly through all regions of the world. COVID 19 has wreaked social, political and economic havoc everywhere and has shown few signs of entirely abating. The recent development and approval of new vaccines against the virus, however, now provides some hope that we may be coming to the beginning of the end of the pandemic. This volume collects papers from a conference titled Economic Dimensions of COVID 19 in Indonesia: Responding to the Crisis, organised by the Australian National University's Indonesia Project and held online 7-10 September 2020. Collectively, the chapters in this volume focus for the most part on the economic elements of COVID 19 in Indonesia. The volume considers both macro- and micro- economic effects across a variety of dimensions, and short - and long-term impacts as well. It constitutes the first comprehensive analysis of Indonesia's initial response to the crisis from an economic perspective
Keywords: COVID-19 Pandemic, 2020- -- Economic aspects -- Indonesia; Indonesia -- Economic policy